2017
DOI: 10.2174/1389557516666160912180155
|View full text |Cite
|
Sign up to set email alerts
|

Phycobilins and Phycobiliproteins Used in Food Industry and Medicine

Abstract: In addition to the stability, bioavailability and safety issues of purified phycobilins and phycobiliproteins, literature data about their antioxidant, anticancer, anti-inflammatory, immunomodulatory, hepatoprotective, nephroprotective and neuroprotective effects, and their potential use in photodynamic therapy (PDT) are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 228 publications
(404 reference statements)
0
50
0
12
Order By: Relevance
“…Phycobilins are a designation of open chain tetrapyrroles (four pyrrole derivative compound) present as photosynthetic accessory pigment that can absorb light from visible radiation, which is poorly absorbed by the chlorophyll, thus permitting the seaweeds living in deep-water [86].…”
Section: Pigmentsmentioning
confidence: 99%
“…Phycobilins are a designation of open chain tetrapyrroles (four pyrrole derivative compound) present as photosynthetic accessory pigment that can absorb light from visible radiation, which is poorly absorbed by the chlorophyll, thus permitting the seaweeds living in deep-water [86].…”
Section: Pigmentsmentioning
confidence: 99%
“…Other nutrient compounds unique to seaweeds, such as fucoxanthin, phycobiliproteins, phlorotannins, and sulphated polysaccharides have therapeutic effects beyond basic nutrition (Mysliwa-Kurdziel & Solymosi 2017;Pérez et al 2016). These will be discussed below.…”
Section: Lipidsmentioning
confidence: 99%
“…It was found that these pigments are ideal for highly sensitive studies in flow cytometry and immunoassays as well as for the photodynamic therapy (PDT) [16,17]. According to the literature, purified phycobiliproteins have antioxidant, anticancer, antiinflammatory, immunomodulatory, hepatoprotective, nephroprotective and neuroprotective effects [14,15,18].…”
mentioning
confidence: 99%